Socio-philosophical analysis of education as the basis of the social and investment model of the strengthening of the statehood, social identity and elite of Kyrgyzstan - Amantur Aidaraliev; Mukhtarbek M. Madaliev (Frontiers in Education, 2025)
This paper seeks the goal of developing a new – social and investment – model for strengthening statehood, social identity and the elite of Kyrgyzstan. Econometric modeling of the role of education in strengthening the statehood, social identity and elite of Kyrgyzstan based on the data of the official statistics for 2006–2021 is performed. As a result, a close connection between education and other interests in enhancing the statehood, social identity and elite of Kyrgyzstan is substantiated. The key role in this process belongs not to higher but to secondary vocational education. That is why it is set in the basis of the proposed social and investment model of strengthening of statehood, social identity and elite of Kyrgyzstan. The theoretical significance of the authors’ conclusions is due to the most complete description of cause-and-effect relationships of enhancing the statehood, social identity and elite of Kyrgyzstan through the clarification of education’s role in them. The social significance of the paper lies in the rethinking of the theory and practice of strengthening statehood, social identity and elite from the position of sustainable development. The authors’ recommendations support the practical implementation of SDG 1, SDG 4, SDG 9, SDG 10, and SDG 11. The practical significance of the developed social and investment model of strengthening of statehood, social identity and elite of Kyrgyzstan consists in its enhancing the scientific and methodological framework for the practical implementation of the National strategy of development of the Kyrgyz Republic for 2018–2040, adopted by the Decree of the President of the Kyrgyz Republic dated 31 October 2018, No. 221. The developed social and investment model will allow the Kyrgyz Republic to adopt the status of great power and to reach the leading positions in Central Asia in the Decade of Action.